On Potential of Natural and Artificial Particulate Mixtures as Reinforcements in Hybrid Bio-composites - Fong, Ai Ling (Curtin University, 2019)
Efforts have been directed toward developing and characterizing natural fibers and fillers filled hybrid bio-composites through different combinations and modifications of constituent materials that consists of epoxy as matrix, sugarcane bagasse fibers, rice husk ash and nanosilica particulates. The interrelation behaviors between the matrix and the reinforcing phases are obtained through characterizations and experimentation using tensile and flexural tests, scanning electron microscope (SEM), and XRD tests.